Urinary Biomarker CXCL10: Identifying Site-Specific Allograft Inflammation in Renal Transplantation. Issue 3 (March 2018) - George, Roshan P.
Abstract : Among the many biomarkers potentially available, urinary CXCL10 seems to be the most promising one. In this section, the author outlines both the interests of this biomarker but also the caution necessary before accepting its site inflammation property.